Influence of Environmental Social Governance (ESG), Profitability and Capital Structure on Firm Value: Study on Industrial Sector Companies Listed on the IDX for the Period 2020-2022 - Mokhtar, Widad Yuliawati; Kusumastuti, Ratih; Wiralestari, Wiralestari (International Journal of Multidisciplinary Approach Research and Science, 2024)
The faster information spreads, the more important it is for companies to publicize the good and minimize problems that can harm the company's reputation and value. Environmental pollution cases and issues are the reasons why positive information is very attractive to investors. Therefore, this study aims to test (1) Does Environmental Social Governance affect firm value, (2) Does Profitability affect firm value, (3) Does Capital structure affect Firm Value and (4) Does Environmental Social Governance, profitability and Capital structure jointly affect firm value in Indonesia. In this study, the population used was industrial sector companies totaling 56 companies and those used as samples in this study were 49 companies that were consecutively listed on the Indonesia Stock Exchange for 3 years in 2020-2022. The sample of this study was determined by random sampling method. The type of research and data used is quantitative with secondary data. The analysis method used is multiple linear regression analysis and uses SPSS 26 software. The results showed that (1) Environmental Social Governance variables affect firm value, (2) Profitability variables affect firm value, (3) Capital structure affects firm value and (4) Environmental Social Governance, profitability and Capital structure together affect firm value.